THE PERCEPTION OF ACEH DOCUMENTARY TRAINING PARTICIPANTS ON IMPROVING CRITICAL THINKING THROUGH DOCUMENTARY FILM APPLICATION - Rizki Dhian Nushur; Diyana Dewie Astutie (English Education Department, 2021)
The times are progressing rapidly so that the need for critical thinking is increasing. Some experts argue that those who think critically are able to solve problems responsively. Therefore, education practicer take various ways to create nowdays critical generation, as well as the Aceh Documentary (ADC) Foundation in Banda Aceh. The documentary film production training which is conducted annually by the ADC Foundation is believed to be able to improve the critical thinking of the participants. This study aims to determine the perceptions of four participants of Aceh Documentery Foundationabout improving their mindset after attending the documentary film production training. This is a qualitative research. The data for this study was collected from early June to August 2019, which the Data collection techniques used in the research were interview and FGD. The data analysis stage was carried out on September 2019 after the documentary film training was completed. The data analysis is carried out by using the Miles & Hubermen style, in which activities in the analysis include data reduction, data display, and conclusion drawing / verification. From this research, it can be concluded that the use of documentary films as a learning medium can improve the participants' critical thinking, eventhough the level of criticism obtained by each individual is different.